Preterm birth is strongly affected by the glucocorticoid dose during pregnancy in women complicated by systemic lupus erythematosus - Hiromi Shimada; Risa Wakiya; Kenji Kanenishi; Nobuyuki Miyatake; Shusaku Nakashima; Mai Mahmoud Fahmy Mansour; Mikiya Kato; Taichi Miyagi; Koichi Sugihara; Yusuke Ushio; Rina Mino; Mao Mizusaki; et al. (Arthritis Research & Therapy, 2022)
Abstract Background This study aimed to investigate the effect of glucocorticoid doses on adverse pregnancy outcomes (APOs) in women complicated by systemic lupus erythematosus (SLE). Methods We investigated 74 pregnancies complicated by SLE or SLE-dominant mixed connective tissue disease. The pregnancies were managed from conception to delivery in our institution. We retrospectively evaluated whether the mean glucocorticoid dose during pregnancy is associated with APOs, including preterm birth (PB), low birth weight (LBW), and light-for-date (LFD). We also calculated the cut-off dose of glucocorticoid that affected APOs. Results All APOs occurred in 35 (50.7%) patients, with 14 cases of PB, 23 cases of LBW, and 10 cases of LFD. Patients with all APOs or PB had a higher dose of glucocorticoid during pregnancy than patients without all APOs or with full-term birth (P = 0.03, P <  0.01, respectively). Logistic regression analysis for all APOs and PB showed that the cut-off values of the mean glucocorticoid dose were 6.5 and 10.0 mg/day, respectively. Patients who delivered LBW or LFD newborns showed no significant difference in the glucocorticoid dose used during pregnancy than patients without LBW or LFD newborns. Patients who delivered LBW newborns were more likely to have used glucocorticoids during pregnancy (P <  0.01). Conclusions In pregnancies complicated by SLE, a relatively lower dose of glucocorticoid than previously reported is significantly related to APOs, especially PB. Therefore, the disease activity of patients with SLE should be managed with the appropriate lower dose of glucocorticoid during pregnancy.